2019
DOI: 10.1002/jcp.29001
|View full text |Cite
|
Sign up to set email alerts
|

Apelin/APJ system: A novel promising target for neurodegenerative diseases

Abstract: Neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD), are incurable diseases characterized by progressive loss of cognitive or motor function, which construct a serious threat to the life quality of aging populations and their life spans. Apelin is an endogenous ligand for the G protein-coupled receptor. Apelin is reported to be detected not only in the cardiovascular system but also in neurons of the central nervous system (CNS).In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 236 publications
(321 reference statements)
0
26
0
Order By: Relevance
“…Moreover, the apelin domain was also significantly enriched by the genes identified from mRNA expression ( p = 1.15 E −2). Apelin has been proposed as a promising target for AD 26 , 27 . Apelin are expressed in various parts of the central nervous system in humans 28 and plays an important role in the pathogenesis of AD 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the apelin domain was also significantly enriched by the genes identified from mRNA expression ( p = 1.15 E −2). Apelin has been proposed as a promising target for AD 26 , 27 . Apelin are expressed in various parts of the central nervous system in humans 28 and plays an important role in the pathogenesis of AD 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effects of apelin on muscle metabolism are probably mediated by the stimulation of AMP-activated protein kinase and Akt and the resultant mitochondriogenesis [13,27]. Downregulation of apelin in mice exhibited age-dependent decline in multiple organs, whereas systemic restoration of apelin improved cognitive and cardiovascular dysfunction, resulting in increased mammalian health span [8,9,11,12,28]. Because these physiologic alterations including musculoskeletal weakness and neurodegeneration are major manifestations of frailty, apelin could be expected not only as a therapeutic target to slow or reverse aging process but also as a clinical biomarker to assess the frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…Apelin is an active endogenous peptide that acts via G protein-coupled apelin receptor (APJ) to exert diverse functional effects [7]. This pleiotropic molecule is involved in multiple biologic processes, including cardiovascular regulation, neuroprotection, immunity, and glucose metabolism [8][9][10]. Apelin has been recently receiving great attention as a promising target for antiaging intervention, primarily based on results from genetically altered mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, APLN inhibited the excitotoxicity mediated by N-methyl-D-aspartic acid (NMDA) receptor in the hippocampus of rats (O' Donnell et al, 2007). Apelin may be beneficial to inhibit Alzheimer's disease (AD) pathology by inhibiting the role of Ang II and regulating the PI3K/AKT/GSK-3β signaling pathways to inhibit hyperphosphorylation [58]. The disruption of Ca 2+ homeostasis may be involved in the pathology of neurodegenerative diseases.…”
Section: Apelin In Neurologicalmentioning
confidence: 99%
“…The disruption of Ca 2+ homeostasis may be involved in the pathology of neurodegenerative diseases. APLN shows an inhibitory effect on the development of neurodegenerative diseases by reducing the Ca 2+ concentration caused by increased sarco(endo)plasmic reticulum Ca 2+ -ATPase (SERCA) activity, suggesting that APLN may be a potential target for the treatment of neurodegenerative diseases [58]. It was reported that epilepsy is associated with increased OS, which may increase susceptibility to attention deficit hyperactivity disorder (ADHD) [16].…”
Section: Apelin In Neurologicalmentioning
confidence: 99%